Impact of tone in firm's market performance : a study on the UK FTSE-350 firms - Oliveira, Ana Barbosa (2024)
The aim of this dissertation is to investigate if there is a boost in information when investors analyze the narrative part of annual reports, which mostly include qualitative data. This study tries to determine whether such analysis helps to bridge the gap between numerical financial statements and the actual corporate performance. By delving further into the qualitative parts of these reports, investors hope to acquire deeper insights into the firm’s financials. Additionally, this dissertation also investigates which message has the most relevant information about the future of the company, the Chief Executive Officer, or the Chairman, and if this information has impact on investors decisions. This investigation will oppose two theories: Agency Theory and Stewardship Theory. To accomplish these purposes, textual analysis was used to measure the tone of UK annual reports narratives insert in the Financial Times Stock Exchange 350 Index, contemplating a sample of 2,598 firm-year observations spanning the period from 2013 to 2023. Findings are related to both the tone of the Chairman's and CEO's reports help to explain the company's future performance. However, contrary to expectations following Agency Theory, when both variables were included in the same model, findings suggest that the predictive power of the CEO is higher than the predictive power of Chairman. The current study contributes to financial reporting literature by providing evidence from the UK that both CEO and Chairman disclosures lead to disclosure benefits due to increased information provided to investors and other stakeholders, which helps to mitigate the gap between numerical financial statements and the actual corporate performance.